Características de los glaciares rocosos del área meridional del Batolito de Panticosa (Pirineo oscense - Chueca Cia, Javier (Geographicalia, 2017)
This paper presents some judgments obtained from the study of a group of rock glaciers placed in the southern part of Panticosa Massif. Genetic, morphometric, locational und datational aspects are examined in full detail.